Spark-Discharge-Activated 3D-Printed Electrochemical Sensors - Hernández-Rodríguez, Juan F; Trachioti, Maria G; Hrbac, Jan; Rojas, Daniel; Escarpa, Alberto; Prodromidis, Mamas I (Analytical chemistry, 2024)
3D printing technology is a tremendously powerful technology to fabricate electrochemical sensing devices. However, current conductive filaments are not aimed at electrochemical applications and therefore require intense activation protocols to unleash a suitable electrochemical performance. Current activation methods based on (electro)chemical activation (using strong alkaline solutions and organic solvents and/or electrochemical treatments) or combined approaches are time-consuming and require hazardous chemicals and dedicated operator intervention. Here, pioneering spark-discharge-activated 3D-printed electrodes were developed and characterized, and it was demonstrated that their electrochemical performance was greatly improved by the effective removal of the thermoplastic support polylactic acid (PLA) as well as the formation of sponge-like and low-dimensional carbon nanostructures. This reagent-free approach consists of a direct, fast, and automatized spark discharge between the 3D-electrode and the respective graphite pencil electrode tip using a high-voltage power supply. Activated electrodes were challenged toward the simultaneous voltammetric determination of dopamine (DP) and serotonin (5-HT) in cell culture media. Spark discharge has been demonstrated as a promising approach for conductive filament activation as it is a fast, green (0.94 GREEnness Metric Approach), and automatized procedure that can be integrated into the 3D printing pipeline.